1975
DOI: 10.1007/bf00421011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two weeks' treatment with thioridazine, chlorpromazine, sulpiride and bromazepam, alone or in combination with alcohol, on learning and memory in man

Abstract: Forty paid healthy male students participated in two subacute experiments of 6 weeks each. In the first trial 20 of them received bromazepam, thioridazine, and placebo double blind cross over for 2 weeks each, and in the second trial the active agents administered to the other 20 participants were chlorpromazine and sulpiride. The tests used were paired associate learning with nonsense syllables and digit memory span. Before testing the subjects took either an alcoholic or a nonalcoholic bitter drink. As in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1977
1977
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…Even though TR is about 10 times as potent an a-receptor blocker as CPZ when measured with the rabbit aortic strip method [Liuequist et al, 1975] , this difference was not evident in the present experiments. This was due either to the inhomogeneity of the clinical material comprising chronic schizophrenic patients or to the possibility that the doses used exceeded the 'sensitive range' of the dose-response curve.…”
Section: Discussioncontrasting
confidence: 49%
“…Even though TR is about 10 times as potent an a-receptor blocker as CPZ when measured with the rabbit aortic strip method [Liuequist et al, 1975] , this difference was not evident in the present experiments. This was due either to the inhomogeneity of the clinical material comprising chronic schizophrenic patients or to the possibility that the doses used exceeded the 'sensitive range' of the dose-response curve.…”
Section: Discussioncontrasting
confidence: 49%
“…Chlordiazepoxide lactam was the only drug which alone impaired associative learning. Also alcohol alone, and all the drugs in combination with alcohol retarded learning acquisition.A number of clinical effects of diazepam, such as symptomatic relief of anxiety, sedative effects, and also the effects on sleep and psychomotor perfor mance, are also shared by its metabolites (Randall et al, 1965; Dasberg et ai, 1974; Nicholson étal, 1976; Palva and Linnoila, 1978).In previous studies we have been concerned with the effects of benzodiaze pines on memory functions (Liljequist et al, 1975(Liljequist et al, , 1978. It was observed that the capacity to acquire new material was impaired after diazepam and bromazepam, whereas diazepam facilitated the recall of orderly consolidated material (Liljequist et al, 1978).…”
mentioning
confidence: 99%
“…Some studies have also indicated that chlorpromazine (Turner, 1966;Besser and Duncan, 1967;Hindmarch, 1979, andthioridazine (Szabadi et al, 1980;Theofilopoulos et al, 1984) lower CNS arousal, as evaluated by critical flicker fusion frequency, whereas sulpiride did not (Bartfai and Wiesel, 1986). Chlorpromazine did not, however, significantly affect human memory (Liljequist et al, 1975(Liljequist et al, , 1978.…”
Section: Introductionmentioning
confidence: 68%